The Psychographic Analysis Of Malaysian Domestic Travelers. - Mohamed, Badaruddin (2005)

(untitled)
After years focusing on international markets, stakeholders in Malaysian tourism sector now realize that in order to sustain the sector, domestic fundamentals must be strong and local travels must be encouraged. Various international crises like the Tsunami, the terrorist attacks, the spread of diseases have shifted the trend, now domestic tourism is becoming the main focus of attention and Malaysians are now encouraged to take holidays and spend longer at home destinations.